2016
DOI: 10.1016/j.bbamcr.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

TCTP regulates spindle microtubule dynamics by stabilizing polar microtubules during mouse oocyte meiosis

Abstract: Dynamic changes in spindle structure and function are essential for maintaining genomic integrity during the cell cycle. Spindle dynamics are highly dependent on several microtubule-associated proteins that coordinate the dynamic behavior of microtubules, including microtubule assembly, stability and organization. Here, we show that translationally controlled tumor protein (TCTP) is a novel microtubule-associated protein that regulates spindle dynamics during meiotic maturation. TCTP was expressed and widely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Specifically, the developmental expression of TCTP in the rat and human testes were studied by the group of Sanchez and Hochstrasser in Geneva (Guillaume et al 2001), and the importance of TCTP as a Ca 2+ -binding protein in the prostate (Arcuri et al 2004) and the placenta (Arcuri et al 2005) were demonstrated by Arcuri et al A more recent study showed that TCTP is essential for the implantation of embryos in the uterus of mice ). An important role for TCTP in egg production in nematodes, such as C. elegans, was demonstrated by TCTP knock-down, which severely reduced the number of eggs produced by these worms (Meyvis et al 2009), consistent with the role of TCTP for meiotic maturation demonstrated in mouse oocytes (Jeon et al 2016). 2.…”
Section: Roles For Tctp In Early Developmentsupporting
confidence: 67%
See 2 more Smart Citations
“…Specifically, the developmental expression of TCTP in the rat and human testes were studied by the group of Sanchez and Hochstrasser in Geneva (Guillaume et al 2001), and the importance of TCTP as a Ca 2+ -binding protein in the prostate (Arcuri et al 2004) and the placenta (Arcuri et al 2005) were demonstrated by Arcuri et al A more recent study showed that TCTP is essential for the implantation of embryos in the uterus of mice ). An important role for TCTP in egg production in nematodes, such as C. elegans, was demonstrated by TCTP knock-down, which severely reduced the number of eggs produced by these worms (Meyvis et al 2009), consistent with the role of TCTP for meiotic maturation demonstrated in mouse oocytes (Jeon et al 2016). 2.…”
Section: Roles For Tctp In Early Developmentsupporting
confidence: 67%
“…Localisation of TCTP to the mitotic spindle, particularly the spindle poles, was also reported by other laboratories (Jaglarz et al 2012;Burgess et al 2008;Bazile et al 2009). A very recent paper even demonstrated the importance of TCTP for the meiotic spindle in mouse oocytes (Jeon et al 2016). These authors found that TCTP is predominantly bound to the spindle poles and contributes to the stability of pole microtubules, but not of kinetochore microtubules.…”
Section: Tctp a Microtubule Stabilising Protein At The Mitotic And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…3−5 TCTP has been shown to play indispensable roles in many biological processes, including development, 6,7 cell proliferation, 8,9 cell death, 10−12 immune responses, 13,14 the cytoskeleton, 15−17 protein synthesis, 18,19 the cell cycle, 20,21 malignant transformation, 22 and induction of pluripotent stem cells or apoptosis. 4,23−26 There is growing evidence in the literature to suggest that TCTP is a vital survival factor and a regulator of cell fate determination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The proteins were primarily involved in metabolism, genetic information processing, environmental information processing, cellular processes, organismal systems and human diseases. The upregulated 14-3-3γ protein (gi|6016838) was related to some pathways, including the viral carcinogenesis 20 , cell cycle 21 , Epstein-Barr virus infection 22 , the Hippo signaling pathway 23 , oocyte meiosis 24 and PI3K-Akt signaling pathway 25 , but the downregulated PLK1 protein (gi|21359873) was associated with the cell cycle 26 , the FoxO signaling pathway 27 , progesterone-mediated oocyte maturation 28 and oocyte meiosis 29 .
Figure 5Significantly enriched KEGG pathways of differentially expressed proteins, * p  < 0.05.
…”
Section: Resultsmentioning
confidence: 99%